Isolation, Identification, and Characterization of Bacterial Isolates in Garlic, Ginger, Pepper, and Turmeric Commonly Traded Within Ilorin, Kwara State, Nigeria - A. E. Ajiboye; M. O. Jimoh; B. A. Hammed; T. E. Adesokan (Journal of Applied Sciences and Environmental Management)
Food condiments/spices consisting of leaves, flowers, seeds or stems of plants are food additives that add special aromas and flavors to food thereby increasing its taste but could harbor an array of microbes. Hence, the objective of this paper was to isolate, identify, and characterize the bacterial isolates in food condiments (Garlic, Ginger, Pepper, and Turmeric) commonly traded within Ilorin, Kwara State, Nigeria using various standard microbial techniques. The highest total heterotrophic count (THC) was 21.52 ± 5.31 Cfu/ml obtained from the samples at location A. The highest total coliform count (TCC) was found in garlic sample (6.67 ± 4.93 Cfu/ml) obtained from location B. The highest total Staphylococcus count (TSC) was found in garlic sample (4.00 ± 1.00 Cfu/ml) obtained from location C. The highest Total Salmonella-Shigella Count of (4.67 ± 3.06 Cfu/ml) was found in garlic sample obtained from location A. The highest total fungi count (TFC) was found in pepper sample (4.13 ± 2.06 Cfu/ml) obtained from location A. The presence of various pathogenic bacteria in the food condiments analyzed raises concern on their impact to the health of the consumers and these food spices could also serve as a vehicle for the transmission of disease causing bacteria.